Support for Policies on Entrepreneurship and Self-Employment among Parties and Coalition Governments - Debus, Marc; Tosun, Jale; Maxeiner, Marcel (Politics & policy, 2017)
We argue that political parties take not only the economic conditions into account when developing a position on entrepreneurship and self-employment but also consider the “heritage” of a socialist state, which can influence the preferences of voters regarding this issue area. We test our hypotheses on the basis of an analysis of election manifestos and coalition agreements. We focus on the German case since unification allows for comparing electorates socialized in a market economy in the West German states and in a socialist economy in East Germany by holding the institutional setting constant. The results support our hypotheses that growing economic problems increase the saliency of entrepreneurship and self-employment and that differences between parties exist: Christian democratic and liberal parties emphasize entrepreneurship and self-employment in their manifestos more than green or socialist parties. In addition, governments including Christian democratic and liberals agree on more market-liberal policies in coalition agreements compared to left-wing governments. Related Articles